2016
DOI: 10.17102/cnr.2016.07
|View full text |Cite
|
Sign up to set email alerts
|

Forest Resource Management in the Context of Climate Change Adaptation and Mitigation in Bhutan

Abstract: The Gaur, Bos gaurus Smith, plays an important role in the pyramidal food chain -being an important prey for large carnivores such as tiger, common leopard, and Asiatic wild dog. Presence of Gaur in an area indicates wild and healthy ecosystem. Reduction of global distribution of Gaur by over 80% in the past 100 years, scaling in the IUCN Red List of Vulnerable category shows the species is facing serious threats. The present study assessed the distribution, activity pattern, and abundance of Gaur in the Royal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Similar to Phobjikha, around 90% of the communities depend on potato production and livestock. The study indicated that climate change has reduced precipitation, increased rainfall affecting yield, increased pests and new invasive weed species have colonized pastureland preventing the regeneration of fodder (Suberi et al, 2018).…”
Section: Literaturementioning
confidence: 99%
“…Similar to Phobjikha, around 90% of the communities depend on potato production and livestock. The study indicated that climate change has reduced precipitation, increased rainfall affecting yield, increased pests and new invasive weed species have colonized pastureland preventing the regeneration of fodder (Suberi et al, 2018).…”
Section: Literaturementioning
confidence: 99%
“…Climate change in the Himalayan region can cause cascading effects on socioecological systems, such as indirect extinction due to loss of critical species, an increase in the number of floods, need to further increase the adaptive capacity of different populations (Xu et al, 2009). Otherwise, increased occurrences of fires in blue pine forests (Vilà -Vilardell et al, 2020), negative impacts on food production, such as potatoes, increase in the number of insects considered pests and invasive plants, in addition to the loss of hands young people who abandon agriculture due to the increase in the difficulties of producing food (Suberi et al, 2018).…”
Section: Bhutan Case Study: Glacial Lake Outburst Floodsmentioning
confidence: 99%
“…Historically, the population of the Himalayas has developed its own measures of adaptation to the gradual climate changes of the past (Xu et al, 2009), which may also be occurring in the present times for some effects of climate change. Suberi et al (2018), for example, identified that in agriculture some adaptation measures for more immediate effects are already being developed and implemented by the local population, but there is little local knowledge on how to face these effects in the long term. In fact, other authors such as Choden, Keenan, and Nitschke (2020) consider that investment in education would be a way to reduce inequality and vulnerability of the population of Bhutan.…”
Section: Ecology Of Knowledge In the Cases Raisedmentioning
confidence: 99%
“…Behavioural adaptations were observed amongst pastoral communities, who have changed their grazing locations and timing of animal movement to cope with snowfall uncertainty (Fu et al, 2012;Gentle & Thwaites, 2016;Rayamajhi & Manandhar, 2020). Fodder plantation, seeding of pastures, and purchasing of livestock feed are some of the measures adopted to improve food availability for livestock (Suberi et al, 2018;Wang et al, 2014;Wu et al, 2015).…”
Section: Householdmentioning
confidence: 99%
“…In response to impacts of cryospheric change on water and food shortages as well as other drivers of Reduction in the number of animals (Hussain et al, 2016) Single community Changes in the timing of animal movement (Fu et al, 2012;Gentle and Thwaites, 2016;Rayamajhi and Manandhar, 2020) Multiple communities Replacing large-sized animals with small ones (Macchi et al, 2014) Technological Household Purchase of livestock feed (Suberi et al, 2018); Plantations of fodder species (Suberi et al, 2018) Multiple communities Reseeding of pastures (Wu et al, 2015) Institutional Single community Pooling of resources and labour (Fu et al, 2012;Y. Wang et al, 2014) Multiple communities Formation of herders' committees to regulate grazing (Joshi et al, 2013) Infrastructural Single community Construction of sheds for the animals (Hussain et al, 2016) Multiple communities Construction of sheds and fencing (Wu et al, 2015) change, communities have reduced the number of animals they own (Hussain et al, 2016;Y.…”
Section: Householdmentioning
confidence: 99%